1998
DOI: 10.1212/wnl.51.2.560
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral aneurysmal arteriopathy in childhood AIDS

Abstract: The development of cerebral aneurysmal arteriopathy in childhood AIDS tends to occur after a prolonged delay and is usually followed by death in a short period of time. The etiology for the vasculitis is unknown. Varicella zoster virus may be the etiology in some of the cases because of its potential to cause this pathology and the striking unilateral arterial involvement found in Case 5. HIV vasculitis is also a possibility, as suggested by the detection of HIV protein or genomic material in two of the four a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
113
0
12

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 4 publications
2
113
0
12
Order By: Relevance
“…A thinner media has been reported in entities associated with arterial dilatation in patients with and without HIV. 1,2,6,7 The lymphocytes in the adventitia were seen in equal proportions among groups, making vasculitis a less likely explanation to our results. Disruption of the IEL has been reported in HIV vasculopathy, 1,2,4 but we failed to reproduce this finding.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A thinner media has been reported in entities associated with arterial dilatation in patients with and without HIV. 1,2,6,7 The lymphocytes in the adventitia were seen in equal proportions among groups, making vasculitis a less likely explanation to our results. Disruption of the IEL has been reported in HIV vasculopathy, 1,2,4 but we failed to reproduce this finding.…”
Section: Discussionmentioning
confidence: 52%
“…[1][2][3] Pathological studies on arteries affected by HIV vasculopathy have demonstrated significant arterial media (ie, muscularis) layer disruption characterized by atrophy, fibrosis, and fragmentation of the internal elastic lamina (IEL). 1,2,4 The HIV infection of the smooth muscle cells may underlie the subsequent deterioration of the media. 5 Little is known about arterial wall changes that could precede the development of clinical cerebrovascular events, particularly those related to HIV vasculopathy.…”
mentioning
confidence: 99%
“…Both large and small vessels display marked endothelial hyperproliferation, death, and monolayer disorganization, leading to aneurysms, occlusions, and telangiectasias (3)(4)(5)(6)(7). Strikingly, HIV-1-infected patients also develop an unusually aggressive form of the vascular neoplasm Kaposi sarcoma, suggesting a prominent contribution of HIV-1 in determining the behavior of Kaposi sarcoma cells.…”
mentioning
confidence: 99%
“…The majority of children with human immunodeficiency virus (HIV) infection have neurologi-cal dysfunction but the development of symptomatic cerebrovascular disease is low (1.3%) 1 . Central nervous system (CNS) involvement in pediatric AIDS may be due to primary HIV infection or to secondary complications of immunodeficiency 2 .…”
mentioning
confidence: 99%
“…The proposed mechanisms for cerebrovascular disease in childhood AIDS include hypoperfusion, septic or thrombotic emboli, and infectious vasculitis of intracranial vessels 3 . It has been discussed whether the vasculitis is directed related to HIV or secondary to associated infections such as herpes simplex virus (HSV), cytomegalovirus (CMV), varicella zoster virus (VZV), mycobacteria, or fungi 1,3,4 . Cerebral artery aneurysms confined to large arteries of the circle of Willis have been previously described in HIV infected children, but a longer latency period following infection was necessary before onset of neurological symptoms.…”
mentioning
confidence: 99%